A novel approach to assess resilience of energy systems. Issue 2 (8th June 2015) - Matzenberger, Julian; Hargreaves, Nigel; Raha, Debadayita; Dias, Priyan
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to outline different notions of the term resilience used in scientific disciplines and consequently explore how the concept can be applied to energy systems. The concept of resilience has emerged recently in scientific discourse. The major questions to be addressed are: Which definitions and underlying concepts of resilience are used in the scientific literature? How can resilience be defined with respect to energy systems and which underlying principles can be identified? Design/methodology/approach – Building on this understanding, characteristics of the resilience concept used in various contexts are described and a methodology for selection of an indicator set for an energy resilience assessment is presented. The methodology for a resilience assessment outlined in this paper requires definition and clustering of a set of indicators describing a resilient system. It contributes to understanding system properties and supports the theory of how to improve system resilience. Findings – It is argued that resilience can be defined as a function of vulnerability and adaptability, therefore increasing adaptability or reducing vulnerability can cause higher system resilience. Further attributes, determinants and properties of resilient systems to guide indicator selection and classification are suggested. Originality/value – Definitions of resilience, vulnerability and adaptability are very much interlinked. A novel framework is proposed to foster the understanding of the interlinkage between these three terms and to cluster indicators to assess energy system resilience.